Pengelolaan Sampah Anorganik di Kelurahan Tlogosari Kulon Kota Semarang - Marshush, Ummi Hanifah; Abubakar, Endang; Rahmatullah, Azwar (AJAD : Jurnal Pengabdian kepada Masyarakat, 2023)
Population growth has an impact on increasing waste production. Semarang City produces 1,110 tons of waste per day. One of the efforts made by the Environmental Service (DLH) regarding waste management is by running a waste bank program. However, this program has not been implemented in all regions. Like in Tlogosari Kulon Village, there is no existing waste bank group running this program. Even though this area is a densely populated residential area and is an area prone to flooding. Therefore, this service is carried out to provide understanding and knowledge regarding waste management, especially inorganic types, and carry out simple actions. The method used is descriptive qualitative. The result of this activity is that there is an understanding of waste management as evidenced by the action of collecting waste according to mutually agreed inorganic waste criteria, reusing gallons and plastic cups as planting media, and plastic bottles as decoration.